2014
DOI: 10.4322/acr.2014.005
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset opsoclonus-myoclonus-ataxia syndrome as a manifestation of brazilian lyme disease-like syndrome: a case report and review of literature

Abstract: Described in 1962, the opsoclonus-myoclonus-ataxia syndrome (OMAS) is a rare, neurologically debilitating disorder with distinct characteristics that may begin in childhood or adult life. Although many cases remain without etiological diagnosis, others are related to neoplasms and infectious diseases. We report a 41-year-old previously healthy male with an 8-day history of headache, vertigo, nausea, vomiting, and nystagmus. After a normal brain computed tomography and lymphocytic pleocytosis in cerebral spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The pathophysiology of OMS is not definitively understood. It has been suggested that antibodies against cell surface or intracellular structures of the nervous system, such as anti-hu, anti-ri, and anti-yo may play a role in OMS (Lino et al, 2014). Specifically, a finding of anti-ri antibodies in a patient presenting with OMS is highly specific for an underlying neoplasm (Jongen et al, 1998, Luque et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of OMS is not definitively understood. It has been suggested that antibodies against cell surface or intracellular structures of the nervous system, such as anti-hu, anti-ri, and anti-yo may play a role in OMS (Lino et al, 2014). Specifically, a finding of anti-ri antibodies in a patient presenting with OMS is highly specific for an underlying neoplasm (Jongen et al, 1998, Luque et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The first manifestation is often EM as in classic Lyme disease; however, there are epidemiological, clinical and laboratory-related differences to define the Brazilian Lyme-like disease, which in 1993 was named Baggio-Yoshinari syndrome (BYS) [250]. In a study of 19 patients, Yoshinari reported that about 30% had skin lesions, 30% arthritis and 42% had neurological disorders; ocular symptoms were observed in 37.5% of patients, especially in the initial phase of the disease [251,252]. BYS is caused by a Borrelia which resembles Borrelia burgdorferi in clinical and laboratory characteristics.…”
Section: Borrelia Lyme Group-baggio-yoshinari Group (Bys): the Brazilian Lyme-disease-like Illnessmentioning
confidence: 99%
“…[ 8 ] Adult-onset opsomyoclonus occurs in 1–2 people/10 million/year, with a 2012 review spanning 65 years at Mayo Clinic, Minnesota, identifying 137 patients. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%